A Syntactico-Pragmatic Study of the Speech of Mild Mentally Retarded Children - Astuty, Astuty; Wulandari, Ayu (The Journal of Educational Development, 2019)
Research on the speech of mild mentally retarded children from the syntactic and pragmatic perspective has not been widely conducted. Research on the speech of mild mentally retarded children was commonly conducted from the phonological perspective. This has encouraged this researcher to conduct this study. Despite experiencing various limitations, mild mentally retarded children are still categorized as children who can be educated to become semi-skilled workers. To become semi-skilled workers, they need good and polite language skills. The purpose of this study is, syntactically, to find out sentences structures, sentences types, and average length of speech and, pragmatically, to find out speech types and politeness that can be maximized in the utterances of the mild mentally retarded children. This is a qualitative study employing a cross-section method. The research subjects were 13 mild mentally retarded children. The research data were in the form of fragments of stories and conversations drawn through recording techniques, noting, observing proficient free involvement, and observing the involvement in skill for approximately three months. The data were analyzed using the pragmatic and syntactic techniques. The findings of this study: Syntactically, this study found speech using sentence structures of S-P, S-P-A, A-S-P-A, A-S-P, A-S-A-P, S-A-P, A-S-P-Ag; S-P-Ag; the sentence types found are simple sentences; and the MLU of 6.94. Pragmatically, there are types of (1) constative, (2) locutionary, (3) representative, directive, expressive, (4) directive, and (5) literal speeches; the observance of the tact maxim, agrement maxim, and generosity maxim and the violation of the tact maxim, the approbation maxim, the modesty maxim, and the sympathy maxim.. To minimize politeness violation, it is recommended that further research be conducted in larger amount of subjects in a longer period of time.